Placating: Satir’s Argument with African Spouses of Nigerian Prisoners as a Pinch of Salt - Adetunji, Christian Matthew; Wambugu, Anne Gathoni (Journal of Applied And Theoretical Social Sciences, 2025)
Introduction: This qualitative phenomenological study applies Virginia Satir's Personal Iceberg Model to explore placating behaviours among the African spouses of incarcerated Nigerian men. Satir conceptualised placating as an incongruent stance characterised by excessive compliance and self-negation. Method: Drawing on the hermeneutic phenomenology of semi-structured interviews and two focus-group discussions with 10 Yoruba women, this paper reinterprets placating within African cultural contexts that valorise endurance, harmony, and moral loyalty. Results or Findings: These findings show that placating is an essential component of Yoruba cultural traditions, promoting flexibility and noble interrelatedness. Discussion or Conclusion: Viewing this viewpoint (the Yoruba cultural-context perspective) via a different lens, such as Satir's, may result in a misconception. The study advances a culturally contextualised reading of Satir's humanistic theory and highlights its implications for cross-cultural family therapy.